Institutional responses to unemployment: a comparison of U.S. trends, 1948-1985 - Inverarity, James (Contemporary crises, 1989)
Previous studies that consistently find a direct effect of unemployment on imprisonment fail to consider other state policies that may be related both to unemployment and imprisonment. This ommission potentially biases in unknown ways the estimated effect of unemployment. This study uses postwar U.S. time series data to examine how the effects of unemployment on imprisonment are influenced by mental institutionalization, military enlistments and welfare rolls. No evidence of trade-offs in social control policies can be detected in these data, thus supporting the previous findings that unemployment directly affects prison admissions.